Making wine safer: the case of ochratoxin A - Kozakiewicz, Z. (2004)
This study aims to assess the risk of ochratoxin A (OTA) in European wine with the objective of reducing toxin levels through an integrated management of production and processing. All European countries of the Mediterranean basin are involved. Preliminary results indicate that OTA producing fungi are already present on grapes in the vineyard, prior to harvest. Vineyard location has more influence on OTA levels than grape variety. Weather patterns also seem to influence OTA levels. Results obtained from applications of various adjuvants aimed at reducing and/or eliminating OTA in wine are discussed.